Does anyone know how to find the GCF when turning a trinomial into a binomial pair? For example the problem 2x^2 + 2x - 12 = 2(x^2 + x - 6) Then I do the 2 by 2 punnet square chart and I put the x^2 in the first box and the -6 in the last box but how do I figure out what goes in the other 2 boxes I know its the 2 factors of the A & C and then I keep the sign of the middle term but how do I get it?
so a = 1 and c = -6 their product is ac = (1)(-6) = -6 b = 1 so find factor of -6 that sum to 1. that is s*t = -6 and s + t = 1
Would it be 3 * - 2
you got it! great job!
Ok but how do I find the GCF of these?|dw:1380729807430:dw|
Join our real-time social learning platform and learn together with your friends!